Law No. 88 of the year 2005 Amending Certain Provisions of Decree-Law No. 89/1960 Concerning Aliens' Entry to, Residence in, and Exit from the Territories of the Arab Republic of Egypt = قانون رقم 88 لسنة 2005 بتعديل بعض أحكام القرار بقانون رقم 89 لسنة 1960 في شأن دخول وإقامة الأجانب بأراضي جمهورية مصر العربية والخروج منها (2025)
Law No. 88 of the year 2005 Amending Certain Provisions of Decree-Law No. 89/1960 Concerning Aliens' Entry to, Residence in, and Exit from the Territories of the Arab Republic of Egypt قانون رقم 88 لسنة 2005 بتعديل بعض أحكام القرار بقانون رقم 89 لسنة 1960 في شأن دخول وإقامة الأجانب بأراضي جمهورية مصر العربية والخروج منها